Dermal Filler types, Effect on soft tissue and Life Style correlation - Mohamed, Dalia A (Journal of Medicine and Health Sciences Research, 2020)
One of the most common manifestation in our time, especially among girls, is those procedures on the skin or maintaining or to modify some of the changes in the skin, such as those that come due to aging or any other cosmetic reasons. Fillers and Botox are two of the most popular procedures. Dermal fillers are effective treatments used to soften and reduce wrinkles and deep lines, fill out the cheeks and smooth facial contours. There are four main types of injectable dermal fillers, including fat, collagen, hyaluronic acid, and microsphere-containing carriers of another material such as polymethyl methacrylate (PMMA). So that to understand any type of injection, it is important to look at its history for valuable lessons and for successful progress. Honestly, it is very interesting to see what and where the world gets in the last 40 years of injectable. Today, we will be examining the brief history of dermal fillers from their bovine collagen roots, to the advanced fillers that are available today. In this review, we aimed to show some types of dermal fillers including a variety of its complication in soft tissue. Also, we try to correlate the factor of lifestyle with its variant effects.